Webtoon’s Effect on Students’ Reading Comprehension at School - Rafida, Tien; Ananda, Rusydi; Suwandi, Suwandi (SCAD Independent, 2023)
This study investigated the effect that employing the Predicting Strategy with Webtoon would have on MTsS Awaliyah students' reading comprehension during the academic year 2021-2022. This study was conducted using a quantitative methodology and a real experimental pretest-posttest control group design. Eighth-grade enrollment was 60 pupils, who were equally distributed between two classes. The samples were comprised of the whole population and were chosen using a simple random selection technique. There were 30 pupils in both the experimental class (VIII-A) and the control class (VIII-B) (VIII-B). The pre-test and post-test each consisted of 20 multiple-choice questions, and they served as the data collection instruments. Using 58 degrees of freedom (df) and a significance threshold of 0.05, a t-test revealed that the value of to was 6,515, and that ttable was 1,673. This equation indicated that to is more than ttable (6,515 > 1,673). According to the study's findings, the alternative hypothesis (Ha) should be accepted, whereas the null hypothesis (Ho) should be rejected. It suggests that the experimental class scored differently than the control class after the therapy was administered. The Predicting Approach with Webtoons has a major impact on students' reading comprehension.